Essential methods in symbolic interaction - Chen, Shing-Ling S. (Studies in symbolic interaction, 2025)
Over the course of more than seventy years, symbolic interactionism as a resourceful and conceptually rich perspective has generated variegated lines of research. In Essential Methods in Symbolic Interaction, symbolic interactionists who adopt different methods in their research articulate the methodological issues critical to their research. Methods discussed include Grounded Theory method, qualitative laboratory method, qualitative media analysis, music research, as well as the use of statistical methods in symbolic interaction research. Volume 60 of Studies in Symbolic Interaction is a forum for symbolic interactionists to "duke it out" regarding the equally critical methodological issues to symbolic interactionist research. Essential Methods in Symbolic Interaction is not only important to clarify the definition of symbolic interactionist research and, by extension, to clear up the ambiguity associated with doing such research but is also crucial to help symbolic interactionists navigate their research activities as they move into new frontiers such as, for instance, providing an interactionist strategy to conduct research in the digital age.